Analysis of Enterococcus faecalis isolates from intercontinental sources by multilocus enzyme electrophoresis and pulsed-field gel electrophoresis. - Tomayko, J F (1995)
Pulsed-field gel electrophoresis (PFGE) and multilocus enzyme electrophoresis (MLEE) were compared in this study of 65 Enterococcus faecalis isolates recovered over a 20-year period from diverse geographic sources. Clonal relationships recognized by PFGE were also recognized by MLEE; however, MLEE recognized as greater number of isolates as belonging to clonal groups than did PFGE. Both techniques were reproducible and discriminatory, but MLEE more readily recognized relationships among large numbers of isolates. MLEE confirmed the previously reported clonal spread of beta-lactamase-producing E. faecalis to six hospitals in five states. MLEE provided a useful population framework of the E. faecalis isolates in this sample, while PFGE was able to differentiate among isolates within some MLEE clonal groups.